2018
DOI: 10.1016/j.niox.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine protects against diabetic nephropathy through control of oxidative and nitrosative stress by recovery of nitric oxide in rats

Abstract: The diabetes mellitus (DM) induces several changes, with substantial increase of reactive oxygen species (ROS). The ROS cause damage to systemic and renal microvasculature, which could be one of the mechanisms involved in the development of diabetic nephropathy (DN). The ROS modulate other substances like the nitric oxide (NO), a vasodilator with important role in the renal function. N-acetylcysteine (NAC) is an antioxidant that acts replenishing intracellular cysteine levels, which is essential for glutathion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…As in other aging-related conditions [28,47], higher levels of ROS seem to be involved in ET-1-induced myoblast senescence because the effect disappeared in the presence of NAC. NAC is an antioxidant that acts replenishing intracellular cysteine levels, which are essential for glutathione formation, responsible for detoxify hydrogen peroxide [48]. Furthermore, NAC also prevented FN expression induced by ET-1 treatment.…”
Section: Agingmentioning
confidence: 99%
“…As in other aging-related conditions [28,47], higher levels of ROS seem to be involved in ET-1-induced myoblast senescence because the effect disappeared in the presence of NAC. NAC is an antioxidant that acts replenishing intracellular cysteine levels, which are essential for glutathione formation, responsible for detoxify hydrogen peroxide [48]. Furthermore, NAC also prevented FN expression induced by ET-1 treatment.…”
Section: Agingmentioning
confidence: 99%
“…ROS plays a crucial role in the aetiology of abnormal embryo development of mammal species throughout pregnancy (Lan et al, 2019). Extensive research in experimental animals and humans has shown that NAC treatment has protective effects for treating multiple disorders and helps control oxidative stress by increasing NO production (Buhimschi, Buhimschi, & Weiner, 2003;Nogueira et al, 2018). The results in the current work showed that the dietary 0.07% NAC supplementation F I G U R E 1 GO enrichment and KEGG pathway analysis of differentially expressed genes (DEGs) of endometrial tissues between the 0.07% NAC and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…It was originally used as a mucolytic agent in treating respiratory diseases. NAC is also an ROS scavenger, which not only serves as an antioxidant and maintains the redox balance in cells [22] , but also inhibits apoptosis [23] , reduces inflammation response [24] , and is widely used for treating cardiovascular system diseases. Recchioni et al [8] showed that NAC could inhibit HG-induced apoptosis in human large aortic endothelial cells.…”
Section: Discussionmentioning
confidence: 99%